Analisis Komparatif Usaha Tani Ubi Jalar (Ipomoea Batatas L.) Varietas Ubi Ungu Dan Ubi Cilembu Di Kecamatan Tawangmangu Kabupaten Karanganyar - Luthfia Andriastutui; Wiwit Rahayu; Indah Nurhidayati (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2025)
Sweet potatoes are one of the non-rice carbohydrate food sources with high nutritional value and are widely cultivated in highland areas, such as Tawangmangu District, Karanganyar Regency. Two dominant varieties grown by farmers are purple sweet potato and Cilembu, which have different characteristics, market values, and economic potentials. This study aims to compare the production costs, revenues, income, profits, and farming efficiency between these two varieties. A descriptive-analytical method was employed, and 60 respondents were selected using a purposive sampling technique. The results show that the average total production cost for purple sweet potato farming was IDR 19,841,805/Ha/ season, while Cilembu required IDR 21,930,730/Ha/ season. Average revenues reached IDR 49,225,385/Ha/season for purple sweet potato and IDR 75,448,102/Ha/season for Cilembu. The respective incomes were IDR 34,921,959/Ha/ season and IDR 57,976,135/Ha/ season. The profits obtained were IDR 29,383,581/Ha/ season for purple sweet potatoes and IDR 53,517,372/Ha/ season for Cilembu. Efficiency values (R/C ratio) of 2.54 and 3.51 indicate that both varieties are feasible and profitable to cultivate, with Cilembu demonstrating higher economic efficiency.